Temporal and spatial characteristics of harmful algal blooms in Qingdao Waters, China - 袁涌铨 俞志明 宋秀贤 曹西华 (Chinese journal of oceanology and limnology, 2017)
Qingdao waters, including both the semi-enclosed Jiaozhou Bay （JB） and the adjacent water out ofJB （OJB）, have been the areas that are most frequently affected by harmful algal blooms （HABs） in the western Yellow Sea （west of 124°E）. In this research, HAB occurrences in Qingdao waters from 1990 to 2009 were investigated using spatial tools in geographic information system （GIS） and are discussed in terms of their connection to temporal variation. Additionally, the effects of each HAB occurrence were further evaluated using a simple model. The calculated results were then visualized using a GIS software to indicate the effects of HABs in Qingdao waters during the entire period. As a result, the OJB was proven to be responsible for the frequent HAB occurrences in Qingdao waters after 2000, although JB was traditionally believed to be the principle source of HAB occurrences in Qingdao waters. In addition, increasing nitrogen and N/P structure imbalance were essential for increasing HAB occurrences in Qingdao waters throughout the entire period, especially for the recent HAB occurrences in the OJB. The results of this research would improve the current understanding on HAB occurrences in Qingdao waters, which would benefit HAB monitoring and the implementation of a control strategy in China as well.